Diversity of Arbuscular Mycorrhizal Fungi in Duabanga Rhizosphere (Duabanga moluccana Blume.) in South Konawe Regency - Tuheteru, Faisal Danu; Husna, Husna; Arif, Asrianti; Hidayati, Ayu; Zainun, Mariana; Nurdin, Wiwin Rahmawati (SINTA Journal (Science, Technology, and Agricultural), 2024)
Arbuscular mycorrhizal fungi (AMF) belong to endomycorrhizae and are symbiotic with nearly 90% of plants. Studies on the diversity of AMF with the Duabanga tree species (Duabanga moluccana Blume.) Have not been widely reported. This study aims to determine the diversity of arbuscular mycorrhizal fungi (AMF) in Duabanga plants in Konda District, Konawe Selatan Regency. Soil and plant root samples were taken in Konda District, Konawe Selatan Regency, Southeast Sulawesi Province. Observations of root colonization, isolation and identification of AMF were carried out at the plastic house of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi Branch, Kendari City, Southeast Sulawesi Province, for 4 months. The results showed that the two dwarf plants were colonized by AMF. The types of AMF found were 5 types of spores from the genus Glomus. The AMF structures found are internal hyphae, external hyphae and vesicles. The diversity of AMFÂ is in the low category.